Microbiology of Cerumen Bacterial Flora of Acute Otitis Externa Patients - Syed Ali Naqi (Journal of Rawalpindi Medical College, 2016)
Background:To compare the microbiology of Cerumen bacterial flora in acute otitis externa patients and healthy individuals. Methods: In this comparative study a total of 120 participants were included, consisting of 50 patients of acute otitis externa patients and 70 healthy participants. Healthy cases without any medical problems but with cerumen in the ear canal were enrolled ascontrol group. Clinical examination of the ear was performed and the patients’ medical history was fully reviewed. Cerumen samples were obtained from both groups by suction, curettage or the use of a loop. Samples were then cultured on chocolate agar, blood agar and eosin methyl blue (EMB) media. The chocolate agar and EMB agar were incubated for 18-24 hrs at 37oC while the blood agar was incubated for 18-24 hrs at 37oC under Co2 condition. Colonies characteristics were then examined by direct microscopic examination (gram staining) and also special diagnostic tests. A p-value equal to or less than 0.05 was considered as significant. Results: Proportion of pathogenic bacteria was significantly (p-value = 0.000) higher in cases of otitis acute externa patients (44% vs. 8.57%) as compared to normal healthy patients. There were significantly (p-value < 0.05) higher gram negative bacteria in cases of otitis externa as compared to healthy control group. Most common microorganisms found in the patient group were Staphylococcus aureus (24.6%), Bacillus (21.2%) and Pseudomonas(9.0%). Staphylococcus epidermidis (41.5%), Diphtheroid (24.7%) and Streptococcus (19.5%) were the commonly found microorganisms in the control group. There was significant (p-value < 0.05) association between colony count and actue otitis externa status. Conclusion: Isolated bacteria from cerumen of healthy subjects were different in comparison to those of acute otitis externa patients